SEM analysis of working surface in new manual endodontic instruments - Jovanović-Medojević Milica; Pelemiš Martina; Nešković Jelena; Popović-Bajić Marijana; Stratimirović Đorđe; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2020)
Introduction The aim of this study was to analyze working surfaces of new hand endodontic instruments and to check possible existence of dirt or defects on working surface that resulted from manufacturing process using SEM. Material and methods Three sets of new hand instruments: K-File (KF), (18 instruments) (Dentsply Maillefer, Switzerland) and Hedstorm Files (HF), (18 instruments) (SybronEndo Co, USA) were used. Instruments were analyzed by SEM method at 170× magnification while semi-quantitative EDS analysis was used to determine chemical composition of dirt particles. Fisher test (p < 0.05) was applied in statistical analysis. Results Results showed that none of the instruments was defect-free. The most common defects were metal strips and fretting noticed at the surface of all tested instruments. Debris was present on all KF (100% in apical and middle third) and HF (56% in apical and 56% in middle third) instruments. Pitting was noticed in KF (33% in apical and 39% in middle third) and HF (11% in apical and 6% in middle third) instruments. Corrosion of working surface, metal flash and disruption of cutting edge were marked only in KF group. Conclusion Manufacturing defects were noticed in all instruments and the most common type of irregularity were metal strips and fretting.